Development of financial technologies and modern trends in the banking sector - Y.I. Burtsev (Економіка, управління та адміністрування)
Investigating the impact of financial technologies on banking reveals the importance of the development of this segment in the context of a rapidly changing financial landscape. Modern technologies are transforming not only the way financial services are provided, but also the very nature of financial relationships.